Stabilitas Ekosistem Hutan Indonesia dalam Menghadapi Deforestasi dan Kerusakan Lingkungan: Tinjauan Literatur - Rahmawati A. Damiti; Parid Pakaya; Mawardi Heru Prasetyo; Dewi Wahyuni K. Baderan; Ramli Utina (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Indonesia is one of the countries with the highest levels of biodiversity in the world and possesses vast tropical forest areas that play a crucial role in maintaining the stability of global ecosystems. However, in recent decades, Indonesia’s forests have faced significant pressures due to deforestation and environmental degradation, which have broad impacts on ecological functions, climate balance, and the socio-economic lives of communities. This study aims to examine the role of biodiversity and ecological adaptation mechanisms in maintaining the stability of Indonesia’s forest ecosystems through a literature review approach. The findings show that deforestation directly affects biodiversity decline, habitat fragmentation, disruption of hydrological systems, increased erosion, and carbon emissions. Additionally, illegal activities such as logging and mining exacerbate environmental degradation. Biodiversity is proven to be an important factor in enhancing ecosystem resilience to disturbances, including climate change. Adaptation mechanisms such as the presence of bioindicator species, the formation of ecological corridors, and community participation in conservation can strengthen ecological resilience. Rehabilitation of degraded areas and the implementation of sustainable governance policies are necessary to restore the ecological functions of forests. This study emphasizes the importance of a multidisciplinary and collaborative approach in conservation strategies, supported by strong scientific, social, and institutional frameworks to ensure the sustainability of Indonesia’s forest ecosystems in the future.